An exercise in self-replication: Replicating Shah, Mullainathan, and Shafir (2012) - Shah, Anuj K.; Mullainathan, Sendhil; Shafir, Eldar (Journal of economic psychology, 2019)
•Various forms of scarcity have similar effects.•Scarcity leads to greater focus and over-borrowing.•No evidence that scarcity on one task leads to cognitive fatigue on subsequent tasks. Shah et al. (2012) examined how different forms of scarcity affect attention and borrowing behavior. Results from a series of lab experiments suggested that (1) various forms of scarcity have similar effects on cognition and behavior, (2) scarcity leads to attentional shifts and greater focus (3) scarcity can lead people to over-borrow, and (4) scarcity can lead to cognitive fatigue. Camerer (2018) recently conducted replications of studies from a set of social science papers, and failed to replicate the result on cognitive fatigue from Shah et al. (2012). In this paper, we present high-powered replications of all studies from Shah et al. (2012). We describe which results appear more robust and which results appear to be less robust. We conclude with some thoughts on the value of self-replications.